(untitled) (American International Journal of Education and Linguistics Research, 2021)
The education sector has been through a lot of changes over time. Specially the last few months have caused a lot of reshaping in the education sector of Bangladesh because of the sudden flare-up of Covid 19. The highly inoculable characteristics of this deadly pandemic have caused educational institutions throughout the world to follow a work-from-home policy and espouse e-learning. Exploring more about e-learning has become a new norm nowadays. This paper aims to analyze the impact of e-learning in the education sector and the role of collaboration in enriching e-learning. This study analyzes the challenges and prospects of collaboration in remote learning. Empirical data was gathered from teachers and collaborators from different educational institutions throughout the world. Data is collected from a web survey by using a structured questionnaire. Based on the findings the researchers have suggested some recommendations for better collaboration to make e-learning more interactive, successful, and embellished. The study outcome would add value to the current teaching practices and enable teachers and collaborators to make collaboration more effective.